Biomedical moral enhancement – not a lever without a fulcrum - Persson, I; Savulescu, J (Springer Netherlands, 2017)
We argued in Unfit for the Future that moral enhancement – which might include biomedical moral enhancement – is necessary to solve the coordination problem presented by the amelioration of anthropogenic climate change. Stefan Schlag contends that this proposal is self-defeating because the implementation of biomedical moral enhancement poses the same problems as combatting climate change. We reply that it can be seen that this is not so when it is realized that we can be sufficiently morally motivated to form an intention in advance to act in a certain (moral) way when a situation arises without being sufficiently motivated to follow through this intention when we are in the midst of the situation and actually experience the self-sacrifices this way of acting imposes on us.